Amount of Lipid Peroxidation Products and Catalase Activity in Tenebrio molitor During Prolonged Cold Effect - Gulevsky, A. K.; Relina, L. I.; Grischenkova, E. A.; Ryazantsev, V. V.; Fedulova, E. S.; Kalnitskaya, O. N. (Problems of Cryobiology and Cryomedicine, 2004)
The content of lipid peroxidation (LPO) intermediates such as: conjugated dienes and ketodienes, as well as catalase activity in 8-10 instar larvae of the yellow mealworm Tenebrio molitor was investigated during prolonged cold acclimation. It has been shown that LPO intensity and catalase activity decreased after 1-hour cold acclimation, then a certain increase in the LPO product content and in catalase activity was observed. Afterwards the indices investigated returned to their pre-acclimation level and remained on that level for 5 months.